Replacement impacts of fish meal with corn protein concentrate in diets on growth, feed availability, and biochemical composition of rockfish (Sebastes schlegeli) - Md. Farid Uz Zaman; Sung Hwoan Cho (PLoS ONE, 2025)
Using fish meal (FM) as the predominant protein source in fish feeds for aquaculture operations poses considerable economic costs and ecological concerns. Therefore, feed nutritionists are looking for inexpensive and supply-stable alternatives to FM in fish feeds. This study aimed to assess the impacts of substituting FM with corn protein concentrate (CPC) in the diet of rockfish (Sebastes schlegeli) on the growth, feed availability, biochemical composition, and blood chemistry. Five hundred forty juvenile rockfish were uniformly dispersed into 18 tanks. Six isonitrogenous and isolipidic diets were prepared. The control (Con) diet contained 55% FM. The CPC10, CPC20, CPC30, CPC40, and CPC50 diets were prepared to substitute 10%, 20%, 30%, 40%, and 50% FM with CPC in the Con diet, respectively. Triplicate groups of rockfish received the experimental diets twice daily for 56 days. The weight gain (WG) of rockfish fed the Con and CPC10 diets was significantly (P < 0.001) greater than that of rockfish fed all other diets. Rockfish fed the Con and CPC10 diets exhibited a comparable specific growth rate (SGR) to that of fish fed the CPC20 diet. Feed consumption (FC) of rockfish fed the Con diet was significantly (P < 0.0001) higher than that of rockfish fed all other diets, with the exception of the CPC10 diet. Rockfish fed the Con, CPC10, and CPC20 diets exhibited significantly (P < 0.0001) higher feed efficiency (FE) compared to rockfish fed all other diets. Protein efficiency ratio of rockfish fed the Con diet was significantly (P < 0.001) higher than that of fish fed the CPC40 and CPC50 diets. Rockfish fed the Con diet exhibited significantly (P < 0.01) greater protein retention than rockfish fed the CPC50 diet. However, the biological indices except for hepatosomatic index, biochemical composition, and blood chemistry of rockfish were not significantly (P > 0.05) influenced by FM substitution with CPC in diets. Conclusively, up to 10% and 20% of FM can be substituted with CPC in the rockfish diet without significantly lowering WG and FC, and SGR and FE, respectively.